Human translational studies investigating the neurocognitive effects of 5-HT4 receptor agonism - De Cates, AN (2022)
Major depression is common, costly, and a global cause of significant morbidity. First-line antidepressant medication has a clinically problematic delay before therapeutic efficacy and is ineffective for a subset of those affected. In addition, many patients with depression, as well as other mental illnesses, find that cognitive impairment has a substantial impact on their quality of life and functioning. Cognitive impairment is poorly treated with medication such as antidepressants, and can persist after remission. Based on animal behavioural studies, as well as molecular and neurochemical evidence, 5-HT4 receptor agonism has been suggested to have putative antidepressant effects and to improve cognition. However, there is relatively little evidence in humans demonstrating such effects.